Estudo comparativo do desempenho de um interferômetro de Michelson de fibras ópticas, operando nos regimes: pulsado e CW, baseado em grades de Bragg (FBG) lineares - Sousa, José Rubens Rodrigues de (2009)
In this work we made a comparative study between the pulsed and CW sings. Such a presents study a numerical analysis of the propagation and switching of ultra-short (~2ps) pulsed and CW signs [1], using a Michelson Interferometer (MI) based in optical fibers. In relation to pulsed sing, we analyzed the characteristics such as transmission, crosstalk, extinction ratio and compression factor and for the CW signal we analyzed transmission, crosstalk and extinction ratio. In this study, the device operation, Michelson interferometer, is based on analyzing the behavior of the pulsed and CW signals as a function of the applied phase to the reflection amplitude of one of the Bragg grating. For better analysis the performance of the device, we attributed three different input powers in channel 1 of the device for each kind of signal. In the case of the pump pulse we have: power below the critical switching value (P0=1W), critical switching power (Pc=1.73 W) and power above the critical switching value (P0=1.95W). In the case of the CW signal we have: power below the critical switching value (P0=0.85W), critical power (Pc=1.30 W) and power above the critical switching value (P0=1.54W). Such parameters, objects of study of this dissertation, it presents better results when we worked with the sign CW in comparison with the pulsed sign.